1999
DOI: 10.1042/bj3420691
|View full text |Cite
|
Sign up to set email alerts
|

Iron-dependent regulation of transferrin receptor expression in Trypanosoma brucei

Abstract: Transferrin is an essential growth factor for African trypanosomes. Here we show that expression of the trypanosomal transferrin receptor, which bears no structural similarity with mammalian transferrin receptors, is regulated by iron availability. Iron depletion of bloodstream forms of Trypanosoma brucei with the iron chelator deferoxamine resulted in a 3-fold up-regulation of the transferrin receptor and a 3-fold increase of the transferrin uptake rate. The abundance of expression site associated gene produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 44 publications
4
28
0
Order By: Relevance
“…2). This excess may therefore not be due to the iron deficiency stimulus that results in overproduction of Tf‐R (Fast et al ., 1999; Mußmann et al ., 2003; 2004). It is possible that the deletion of ESAG7 from the ES results in an abnormal processing of ESAG6 and that this explains the very high ESAG6 mRNA levels in these adaptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). This excess may therefore not be due to the iron deficiency stimulus that results in overproduction of Tf‐R (Fast et al ., 1999; Mußmann et al ., 2003; 2004). It is possible that the deletion of ESAG7 from the ES results in an abnormal processing of ESAG6 and that this explains the very high ESAG6 mRNA levels in these adaptors.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the Tf‐R encoded by the so‐called 221 ES binds dog Tf with such low affinity that the trypanosomes are unable to grow on 10% dog serum, unless a tiny amount of bovine Tf (for which the Tf‐R has a high affinity) is added (Bitter et al ., 1998; Gerrits et al ., 2002). T. brucei appears to cope with the Tf deficiency in dilute dog serum in two ways: after transfer from calf to dog serum based medium, there is an immediate 5‐ to 10‐fold upregulation of Tf‐R protein and mRNA levels in the cell, even before cellular iron stores are depleted (Fast et al ., 1999; Mußmann et al ., 2003; 2004). If this extra Tf‐R is not sufficient to restore normal growth, the population is eventually overgrown by trypanosomes that have switched to another ES that encodes a Tf‐R with a higher affinity for dog Tf than the 221 Tf‐R (Bitter et al ., 1998; Gerrits et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Switching to another expression site allows the parasite to express a more suitable TfR (Bitter et al ., 1998; Gerrits et al ., 2002). When starved for iron by treatment with an iron chelator, trypanosomes can upregulate TfR expression (Fast et al ., 1999). We show here that a more physiological form of iron starvation, induced by growth of trypanosomes in serum with a transferrin that is poorly taken up, also induces TfR upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the ESAG 6/7 transferrin receptor can be regulated by iron levels. The mechanism involved has not been identified but differs from the mammalian iron-response system (Fast et al, 1999;Mussmann et al, 2004;van Luenen et al, 2005). The ESAG 6/7 heterodimer is attached to the membrane by a single GPI anchor on the ESAG 6 subunit.…”
Section: Introductionmentioning
confidence: 99%